Information Restrictions of the Russian Concept of Goodwill Accounting and the Vector of its Development - P. P. Baranov; Y. I. Ustinova; A. P. Voewodin (Учёт. Анализ. Аудит)
This article considers the information restrictions preventing users of financial reporting from getting reliable information about such a special resource of a company as goodwill. These restrictions result from lacking accuracy in defining basic notions, non-observance of legal forms and economic contents, subjective presentation and disclosure of the information about goodwill in financial statements. The analysis of these restrictions makes the authors admit that the fundamental contradiction exists in Russian concept of goodwill (business reputation) accounting. De jure the business reputation accounting is on the dynamic stage of its methodology development, providing for recognition of goodwill gained by a company as noncurrent asset, which is subject to straight line depreciation during its long useful life, but de facto the goodwill acquired by companies trading nationally is not recognized on their financial statements, pushing Russian accounting practice back to the statistical phase of development. Thus overcoming of information restrictions under consideration is densely connected with resolving the named contradiction. The research of the key issues of goodwill accounting in the foreign accounting science permitted the authors to define the vector of business reputation accounting concepts development. The authors propose to extend the informative restrictions by reviewing methodology approaches to business reputation accounting and methodic instruments used for this purpose.